PENGEMBANGAN APLIKASI PELELANGAN MENGGUNAKAN FRAMEWORK CODEIGNITER BERBASIS WEB - Yuli Syafitri; Reni Astika; Lusia Septia Eka Esti Rahayu (STMIK Dian Cipta Cendikia Kotabumi, 2022)
One type of sale and purchase transaction that is generally known is an auction transaction. However, many users are dissatisfied with the online auction system for many reasons. The development of information technology at this time has grown very rapidly. One of the benefits of its application is that it is used in the world of trade to help the auction process or buying and selling of goods online to run effectively and efficiently. The advancement of the internet in Indonesia has resulted in the development of the e-auction industry. The proliferation of the e-commerce industry has made it easier for Indonesians to sell. search and buy the desired item. This application is built from the PHP programming language and utilizes the CodeIgniter framework with the Exreme Programming development method. The process of this development stage is divided into six stages, namely: needs analysis, design, implementation, testing and development of the system. At the testing stage, a functionality test is carried out using the BlackBox Testing method, which is to test the function of the application that has been built whether it is in accordance with the needs. From the test results show the application runs well and has a good processing time. Web-based online auction system is a web-based application that was built to make it easier for us to carry out the auction process or buy and sell goods.